FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI, PENDAPATAN DAN KESEMPATAN KERJA PADA USAHA TANI PADI SAWAH DI DAERAH IRIGASI PARIGI MOUTONG - LIEN DAMAYANTI (Universitas Sebelas Maret, 2013)
Access to reliable irrigation water can make farmers use new technologies and intensify land management, which leads to increase productivity, production of paddy, rice farm income and employment opportunities in the paddy fields. This study aims to: (1) analyze factors that influence rice production; (2) analyze factors that influence rice farm income; (3) analyze factors that influence rice farm labor. The experiment was conducted in the District of Parigi Moutong which is purposivelydetermined by consideration that the number of irrigated area in there is quite wide, but rice farm income still relatively low. The respondents in this study were 100 respondents taken from two irrigation conditions namely good irrigation (58 farm households) and damaged irrigation (42 farm households). The data analyzed by using the model of Two Stage Least Square (2SLS).